COD removal from sucrose solution using hydrodynamic cavitation and hydrogen peroxide: a comparison between Venturi device and orifice plate - Alves,Paulo Henrique Lopes (2019)
ABSTRACT The aim of the current study is to compare the chemical oxygen demand (COD) removal efficiency of a Venturi device to that of an orifice plate. The inlet pressure in the devices was optimized and the degradation kinetics was analyzed. In addition, the synergistic effect resulting from the combination between cavitation and H2O2 was investigated. An experimental apparatus was built to achieve these goals. A sucrose solution and an effluent from a sucrose-based soft drink industry were treated. Results showed that the Venturi device recorded 90% COD removal efficiency after three treatment minutes. On the other hand, the orifice plate recorded 90% COD removal efficiency after 9 min. The degradation kinetics-reaction order was 3.5, except for the highest Venturi inlet pressure (7.3 bar), which led to coalescence of cavities and to reduced degradation rate. The synergistic coefficient (Sc) was 185.20 and showed that the hybrid process (HC + H2O2) was much more efficient than the cavitation process applied alone. The high COD concentration in the effluent generated by the soft drink industry (2,512.8 mg L-1) was significantly decreased by 72%. The combined use of cavitation and Venturi has significant potential to remove high organic matter concentrations in short treatment periods.